0716 The Clinical Characteristics And Therapeutic Efficacy Of Catathrenia. (27th May 2020) - Wen, Y; Xu, L; Han, F
Abstract: Introduction: Catathrenia/nocturnal groaning, is a rare sleep disorder characterized by repeated groaning in a protracted expiration preceded by a deep inspiration. The classification was moved from ICSD-2 as parasomnia to sleep-disordered breathing(SDB) in ICSD-3. The pathogenesis of catathrenia is unknown. Methods: To investigate catathrenia's response to continuous positive airway pressure (CPAP) treatment, and its relationship with SDB. We analyzed patients diagnosed at the Sleep Center of Peking University People's Hospital from 2009 to 2016. All patients were confirmed with nocturnal groaning by polysomnography(PSG), and recording of the sounds. The patients were recommended for treatment of CPAP. Results: A total of 49 patients were recruited into this study, including 31 female and 18 male, age ranging from 16 to 64 years. The average onset age was 19.81 ± 8.65 years old, the average BMI was 21.76 ± 2.62 kg/m², the average groaning index (GI) was 11.58 ± 13.32 times per hour, and the average apnea hypopnea index (AHI) was 3.59 ± 8.83 times per hour. The GI in REM and NREM sleep were 39.31 ± 44.39 and 6.74 ± 8.5 times per hour respectively (p <0.01). The GI of 26 patients who received CPAP treatment decreased from 10.57 ± 12.01 to 5.65 ± 7.10 times per hour (p <0.001). Conclusion: Catathrenia occurs mainly in REM sleep, and treatment with CPAP is effective, although cannot be completely eliminated. Suggest that catathrenia might be a sleep breathing disorder Support: There is no support of this study